2013
DOI: 10.1186/2045-3329-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Response to imatinib in villonodular pigmented synovitis (PVNS) resistant to nilotinib

Abstract: BackgroundPigmented villonodular synovitis (PVNS) is a rare locally aggressive tumor. PVNS is characterized in most cases by a specific t(1;2) translocation, which fuses the colony stimulating factor-1 (CSF1) gene to the collagen type VIa3 (COL6A3) promoter thus leading through a paracrine effect to the attraction of non-neoplastic inflammatory cells expressing CSF1-receptor. Imatinib is a tirosin-kinase inhibitors (TKI) active against CSF1-receptor whose activity in naïve PVNS was already described. We report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Likewise, a phase 1b study of PD-0360324 (a human IgG2 monoclonal antibody that inhibits CSF-1 binding to CSF-1R) in patients with cutaneous lupus erythematosus (N = 28) demonstrated target engagement, but no therapeutic effects were observed (Masek-Hammerman et al, 2016). The most promising effects of CSF-1/CSF-1R inhibition have been reported in patients with PVNS, with several studies demonstrating clear therapeutic benefits (i.e., tumor volume regression, objective response, complete response, and symptomatic improvement) (Cassier et al, 2012;Stacchiotti et al, 2013;Cassier et al, 2015;Tap et al, 2015).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Likewise, a phase 1b study of PD-0360324 (a human IgG2 monoclonal antibody that inhibits CSF-1 binding to CSF-1R) in patients with cutaneous lupus erythematosus (N = 28) demonstrated target engagement, but no therapeutic effects were observed (Masek-Hammerman et al, 2016). The most promising effects of CSF-1/CSF-1R inhibition have been reported in patients with PVNS, with several studies demonstrating clear therapeutic benefits (i.e., tumor volume regression, objective response, complete response, and symptomatic improvement) (Cassier et al, 2012;Stacchiotti et al, 2013;Cassier et al, 2015;Tap et al, 2015).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Imatinib mesylate (IM), a tyrosine kinase inhibitor, is the first-line drug of choice for chronic myeloid leukemia (18) and a gastrointestinal stromal cell tumor. A number of recent studies have reported a significant clinical effect of IM on PVNS (1,(19)(20)(21). The effect of IM on PVNS was initially documented by Blay et al (1).…”
Section: Introductionmentioning
confidence: 96%
“…55 Infliximab, an inhibitor of tumour necrosis factor alpha (TNF-alpha), is thought to be effective due to the inflammatory state of synovial tissue in PVNS and the high levels of TNF-alpha. 56 There is evidence that imatinib, a tyrosine kinase inhibitor, may be effective for PVNS by inhibiting the CSF1 receptor, improving symptoms and reducing tumour size [57][58][59] ; toxicity is associated with its chronic use. 58 One of our patients with right-knee PVNS had stable disease after RT and imatinib.…”
Section: Discussionmentioning
confidence: 99%